(untitled) (Can Tho)
This book is included three section: sustainable development and infrastructure, the costs, benefits and risks of infrastructure development, accounting for the social and environmental impacts of infrastructure development.
Keywords: Environmental protection,Infrastructure,Social impact,Environmental impact analysis,Bảo vệ môi trường,Cơ sở hạ tầng,Tác động của xã hội,Phân tích tác động của môi trường